PENGARUH USAHA PENGELOLAAN SAMPAH TERHADAP PENINGKATAN PENDAPATAN KELUARGA PEMULUNG DI KECAMATAN TENAYAN RAYA PEKANBARU - Suryani. H, Ade; Syahza, Almasdi; Johan, Rina Selva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : The born of law Management of Garbage is to alter concept management of our garbage which still conventional during the time. Effort management of arising out garbage causes of generation of UUPS this is Bank of Garbage. As an effort management of garbage, Bank of Garbage apply system save garbage and in running activity on Bank of Garbage cooperate with compiler to collect garbage which later will recycle become valuable goods sell. For certain garbage like tidiness plastic garbage is garbage type which in recycle alone by Bank Garbage. The goal of this research is to know is there any influence of is effort management of garbage like Bank Garbage of Dallang Collection to make up income of compiler garbage family’s becoming depositor client there. This research sampel is entire/all compiler garbage becoming depositor client in Bank Garbage of Dallang Collection amounting to 30 people. Method the used is Quantitative Descriptive method. Data of enquette later;then will be analysed with Test of Chi Square or of Chi Square. From result of processing can know that effort management of garbage like Bank Garbage of Dallang Collection do not have an effect on to make-up of earnings compiler garbage family’s. This matter is proved availably Chi Count < Chi tables of that is 7.8724 < 12.592.Keywords : recycle, income